Contemporary digital sociology in search of meaningmaking models: the proper and the actual. A review of articles from the research handbook on digital sociology edited by Jan Skopek (Edward Elgar Publishing, 2023, 492 p.) Part II - E. V. Andrianova; V. A. Davydenko; A. I. Rozmanov (Цифровая социология, 2025)
The study includes a critical analysis of the last 10 chapters exploring the implications of digital technological change, including social, digital, and educational inequalities. These chapters cover a wide range of research from empirical to interpretive approaches and demonstrate a methodological and theoretical mix of different research orientations. Particular emphasis has been placed on the analysis and practices ofadolescents’ use of information and communication technologies at home and at school, social and economic inequalities in children’s digital literacy from primary to secondary school, adolescent mental health in the context of digital inequalities, gender gap in digital skills, and family matters and concerns in digital era. The price of mental health associated with the use of swipes and dating apps, the interrelationship of social media and well-being at work and at home, home-work-digital interrelationships, the characteristics of the digital transition and its implications for labor markets, the skills development issues in the context of digital transformation, and the impact of digital campaigning and media on elections have been considered. The handbook describes sociological and digital academic fields and assumes that both perspectives are equally legitimate, as they reflect the two academic identities of the vast and heterogeneous academic field called digital sociology. This paper is a continuation of the review of the research handbook on digital sociology edited by J. Skopek.